Accumulation of p53 protein in inverted transitional cell papilloma of the urinary bladder. Issue 1 (February 1996) - Chan, K W; Lam, K Y; Srivastava, G
Abstract : Aims —To study the possible accumulation of p53 protein in inverted papilloma of the urinary bladder. Methods —Formalin fixed, paraffin wax embedded sections from 14 cases of inverted papilloma of the urinary bladder were studied retrospectively. Accumulation of p53 was detected by immunohistochemistry using a mouse monoclonal antibody directed against p53. p53 protein reactivity was scored as follows: 0 = 10%; 1 = 10% to <30%; 2 = 30% to <50%; and 3 = >50% of cells p53 positive. Results —The 14 sections were scored as follows: 3 in four cases; 2 in four cases; 1 in one case; and 0 in five cases. Overall, nine (64%) of the 14 cases were positive for p53 protein. Conclusions —The accumulation of p53 protein in inverted papilloma of the urinary bladder suggests that p53 may have has an important role in the neoplastic process of this tumour. However, the benign nature of inverted papillomas suggests that p53 protein accumulation is not related to tumour invasiveness and metastasis. p53 reactivity cannot be used as a marker of malignancy for urothelial neoplasia. Further studies are required to determine the role of p53 protein in the oncogenesis of urothelial neoplasms.